FLARE: A Framework for the Finite Element Simulation of Electromagnetic Interference on Buried Metallic Pipelines - Arturo Popoli; Giacomo Pierotti; Fabio Ragazzi; Leonardo Sandrolini; Andrea Cristofolini (Applied Sciences, 2023)
The functionality of buried metallic pipelines can be compromised by the electrical lines that share the same right-of-way. Given the considerable size of shared corridors, computer simulation is an important tool for performing risk assessment and mitigation design. In this work, we introduce an open-source computational framework for the analysis of electromagnetic interference on large earth-return structures. The developed framework is based on FLARE—an efficient finite element solver developed by the authors in MATLAB®. FLARE includes solvers for problems involving static electric and magnetic fields, and DC and time-harmonic AC currents. Quasi-magnetostatic transient problems can be studied through time-marching or—for linear problems—with an efficient inverse-Laplace approach. In this work, we succinctly describe the optimization of time-critical operations in FLARE, as well as the implementation of a transient solver with automatic time-stepping. We validate the numerical results obtained with FLARE via a comparison with the commercial software COMSOL Multiphysics®. We then use the validated time-marching analysis results to test the accuracy and efficiency of three numerical inverse-Laplace algorithms. The test problem considered is the assessment of the inductive coupling between a 500 <semantics>k</semantics><semantics>V</semantics> transmission line and a metallic pipeline buried in the soil.